2020
DOI: 10.48550/arxiv.2002.09413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Configuration Entropy for Quarkonium in a Finite Density Plasma

Nelson R. F. Braga,
Rodrigo da Mata

Abstract: In the recent years many examples appeared in the literature where the configuration entropy (CE), introduced by Gleiser and Stamatopoulos, plays the role of an indicator of stability of physical systems. It was observed that, comparing states of the same system, the lower is the value of the CE, the more stable is the state. In this letter we investigate the behaviour of the CE in a new context. We consider quasi-states of quarkonium (a vector meson made of a heavy quark anti-quark pair) inside a plasma at fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Making use of this correspondence many works were done in order to study hot dense QGP [19][20][21][22][23][24], considering finite chemical potentials (or some related topics as for instance, QCD phase transition, chiral symmetry breaking, critical exponents, etc. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]) and quantum or thermal fluctuations such as the Brownian motion [40][41][42][43][44][45][46], fluctuation and dissipation [47][48][49][50][51][52][53][54][55], drag forces [56][57][58][59][60], or related topics [61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Making use of this correspondence many works were done in order to study hot dense QGP [19][20][21][22][23][24], considering finite chemical potentials (or some related topics as for instance, QCD phase transition, chiral symmetry breaking, critical exponents, etc. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]) and quantum or thermal fluctuations such as the Brownian motion [40][41][42][43][44][45][46], fluctuation and dissipation [47][48][49][50][51][52][53][54][55], drag forces [56][57][58][59][60], or related topics [61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [11] demonstrated that the DCE regulates the stability of heavy vector mesonic states against dissociation, in a thermal medium. Additionally, new aspects of AdS black holes have been paved, including the way information is stored in AdS black holes, in the context of the Hawking-Page phase transition and the DCE [12].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39]. We can also mention other works, where the critical points of the CE have been used to explain the phenomena of AdS black holes and their quantum portrait as Bose-Einstein graviton condensates, also emulating magnetic structures [40][41][42][43][44][45]. The measure of the minimum values of CE, or the critical points, carries all information content about the stability of the complex nuclear systems.…”
Section: Introductionmentioning
confidence: 99%